2022
DOI: 10.48550/arxiv.2201.12117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generalized resonance energy transfer theory: Applications to vibrational energy flow in optical cavities

Abstract: A general rate theory for resonance energy transfer is formulated to incorporate any degrees of freedom (e.g., rotation, vibration, exciton, and polariton) as well as coherently-coupled composite states. The compact rate expression allows us to establish useful relationships: (i) detailed balance condition when the donor and acceptor are at the same temperature; (ii) proportionality to the overlap between donor's emission and acceptor's absorption spectra; (iii) scaling with the effective coherent size, i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In a separate line of development, there have been a series of studies that have demonstrated the effective role of external electromagnetic cavities in manipulating material excitations. These studies range from the control of electronic excitations [7][8][9][10][11][12][13][14][15][16], vibrational modes [17,18], collective mode responses [19,20] to the cavity mode-assisted modulation of dynamical resonances [21][22][23][24][25]. Cavity mode interacting resonantly with narrow-band of excitons and off-resonantly with the rest may modulate the excitation dispersal by tuning the delocalization properties and influence the dephasing properties via the spectral weight modulation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In a separate line of development, there have been a series of studies that have demonstrated the effective role of external electromagnetic cavities in manipulating material excitations. These studies range from the control of electronic excitations [7][8][9][10][11][12][13][14][15][16], vibrational modes [17,18], collective mode responses [19,20] to the cavity mode-assisted modulation of dynamical resonances [21][22][23][24][25]. Cavity mode interacting resonantly with narrow-band of excitons and off-resonantly with the rest may modulate the excitation dispersal by tuning the delocalization properties and influence the dephasing properties via the spectral weight modulation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In a separate line of development, there have been a series of studies that have demonstrated the effective role of external electromagnetic cavities in manipulating material excitations. These studies range from the control of electronic excitations [7][8][9][10][11][12][13][14][15][16], vibrational modes [17,18], collective mode responses [19,20] to the cavity mode-assisted modulation of dynamical resonances [21][22][23][24][25]. Cavity mode interacting resonantly with narrow-band of excitons and off-resonantly with the rest may modulate the excitation dispersal by tuning the delocalization properties and influence the dephasing properties via the spectral weight modulation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical understanding of these observations is at present incomplete. Observed chemical consequences of vibrational strong coupling in the electronic ground state and in the absence of incident light still await theoretical descriptions despite recent efforts [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%